Studi Hadis Tentang Wanita Adalah Aurat (Analisis Pendekatan Hermenutika Ma`Na Cum Maghza Sahiron Syamsuddin) - Tia Ningsih; Febriyeni Febriyeni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
In the history of Islam, there is no prohibition for women to do work outside their homes. women have great roles and responsibilities when they do activities outside the home. This is evidenced by the existence of women who participated in wars, worked as nurses, shepherds, babysitters, and many more. Although in Islam it is said that women are siblings of men and women have equality with men, this does not mean that it is used as a barrier between men and women. This research is included in the type of library research, namely understanding the hadiths that discuss women who are active outside the home, especially the hadith that says that women are aurat. When women are outside the home, they should maintain their socialization, maintain their manners, and maintain the clothes they wear so that there is no fitnah which will have a bad impact on women.